PENERAPAN KONSEP NARATIF MELALUI VISUAL PADA FILM FIKSI “CAKHRA KALA” - I Komang Frederich Blessy; I Komang Arba Wirawan; I Nyoman Payuyasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
A narrative storytelling through audio visual that tells about the conflict of a new married couple. Narrative film with the concept of timeloop has uniqueness That means a looping scene that makes the main character could change each action. The concept of timeloop is still rarely used in the Indonesian Film Industry. Therefore, making the concept of timeloop can make a development for the film industry in Indonesia. The concept is packaged by combining a little culture about the elements of locality in the conflicts that occur in the patriarchal system in Bali. The patriarchal system places men as holders of power in the family. Some family life in Bali, which is the backbone is a woman. So narrative and visual will be applied in this writing. The creation of the fiction film " Cakhra Kala " was carried out to find out the process of translating a fictional story into an audio visual work. A concept created using the planning stage and the applied stage method. In the film " Cakhra Kala ", not only audio can deliver narrative stories, but a narrative is explained through images that have meaning. Images that have this meaning will lead the audience to enjoy the story. This narrative theory has reference from David Bordwell’s book named “Narration in the Fiction Film”.The result of this creation is a fictional film " Cakhra Kala " created with a gradual process. It starts with making story ideas, story lines, characterizations, the production process, and the post-production stage. The creation of the fiction film " Cakhra Kala " and narrative visual concept are expected to help the development of the Indonesian film industry in creating a unique story that can be raised and combined in line with the habits of the Indonesian people, especially in Bali.